Ordinary Man / Common Man: Conceptual Subject’ Projections of Everyday Discourse - Kardashova, Helena (Respectus Philologicus, 2015)
This paper seeks to formalize the structures of everyday discourse. The search for factors ensuring the unity and autonomy of everyday discourse is based on the assumption that the integrity of the discourse as such is guaranteed by the instance of discursive subject. The article deals with the common notion of collective subject/common subject popular in lingua-cultural approach in the Russian discourse analysis. The article on the material of the Russian National Corpus analysed the statements containing an identifier “common / ordinary man”, specified the values in this model, and reconstructed the paradigm of conceptual meanings significant to the speaker as the subject of ordinary discourse. Two aspects of the concept are considered: one model focuses on semantic structures of a subject positioned as a member of a community; another model is related to the subject projecting one in opposition to the other. The author of this article argues that the constitutive force of each discursive practice lies in its provision of subject positions. While the everyday discourse makes available to take up both positions for subjects, the discourse analysis reveals the synergistic nature of everyday communication.